Pengaruh Laporan Keuangan Berbasis SAK EMKM dan Perpajakan Terhadap Kinerja UMKM Sabun di Surabaya - Sandari, Tries Ellia; Pandin, Maria Yovita R; Soemadijo, Pramita Studiviany; Djumaifin, Thesalonika; Pranoto, Felix Candra (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this study is to determine the influence of financial statements based on SAK EMKM and taxation on the performance of soap MSMEs. This type of research is quantitative. The population in this study is all soap artisan MSMEs in Surabaya with a sample of 85 craftsmen. The data collection method used questionnaires. The results of the study show that partially financial statements based on SAK EMKM and taxation have a positive and significant effect on the performance of MSMEs with the results Fhitung 154,220 > Ftable 3,108 the Adjusted value of R2 is 0.786 or 78.6 % shows that there is an influence between the SAK EMKM based Financial Statements on MSME Performance of 78.6 % and the rest 21,4 % is influenced by other factors.